Effect of Compression Rotation Intervals on Cardiopulmonary Resuscitation Quality: A Systematic Review and Meta-Analysis - Chinnawudh Sawee; Chaitong Churuangsuk; Veerapong Vattanavanit (Archives of Academic Emergency Medicine, 2025)
Introduction: Reducing the compression rotation interval from 2 to 1 minute is expected to improve cardiopulmonary resuscitation (CPR) quality. This meta-analysis aimed to assess the effect of altering the compression rotation interval on key CPR quality parameters, including compression depth, rate, and rescuer fatigue.